Poverty and informality in Ecuador - Carla Canelas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper uses national representative data from the Ecuadorian Family Expenditure survey to study the determinants of poverty and informality in the country, taking into account the simultaneous two-way relationship between these two phenomena. The results support the view of a heterogeneous informal market, where informal work is both a demand-led phenomenon as well as a voluntary and primarily supply-led form of employment. As such, informal salaried work and self-employment are both a last resort option for low-skilled workers and a voluntary choice for the more educated and entrepreneurial ones.
Keywords: I32; J46; 330; informality; poverty; developing economy